A Study of Leadership Styles in Diverse Organizations Management: Exploring the Impact of Leadership Styles on Organizational Performance in an Oil and Gas Company in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This paper explores leadership styles in diverse organizational in an oil and Gas Company in India. The respondents are employees of an oil and Gas Company in India. This study use Multifactor leadership to define leadership styles and diverse Organizational Culture Model to measure Organizational management. These surveys were used to measure leadership styles of immediate or direct supervisor and organizational management of unit or division. The data were analyzed with descriptive and use correlational analysis. A relationship exists between the leadership styles of immediate or direct supervisor and organizational management. In three Leadership styles of Multifactor leadership, Positive correlation was found between Transformational Leadership Style and Organizational management. Transformational Leadership found as strong predictor of organizational management. A positive correlation also found between Transactional Leadership Style and Organizational management and conversely, Laissez-Faire Leadership style has negative correlation with organizational management in oil and gas industry. Transformational, Transactional Leadership and high level of organizational management was make good impact for maintaining and achieving excellent organizational performance for oil and Gas Company.